1996
DOI: 10.1021/js9602812
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Delivery of Antigens and Adjuvants in Vaccine Development

Abstract: Advances in the understanding of the pathogenesis of infectious diseases and cancer immunology have inspired many new approaches to vaccine development. Many subunit antigens and peptides that are effective for vaccination have been discovered. These subunit antigens in tum stimulate synthesis of effective adjuvants to enhance their immunogenicity. Controlled-release technology offers the potential of further improving the efficacy of conventional vaccine formulations by optimizing the temporal and spatial pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
28
0
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(29 citation statements)
references
References 152 publications
0
28
0
1
Order By: Relevance
“…They need potent adjuvants or immune enhancers which increase the specific immune response to an antigen and induce immune protection [4, [6][7][8].…”
Section: Definition Of Adjuvantsmentioning
confidence: 99%
See 1 more Smart Citation
“…They need potent adjuvants or immune enhancers which increase the specific immune response to an antigen and induce immune protection [4, [6][7][8].…”
Section: Definition Of Adjuvantsmentioning
confidence: 99%
“…Although the exact mechanism of the adjuvant effects is poorly understood it has been demonstrated that an appropriate system can direct antigens into antigen presenting cells (APCs) to generate both cellular and humoral responses [7]. Enhanced potentiation of both the humoral and cell mediated responses appears to playa major role in offering significant protection against infections in mIce.…”
Section: Non Particulate Adjuvantsmentioning
confidence: 99%
“…10 Several controlled release technology materials, including liposomes, polymers, and viruslike particles, have been tested to improve the efficacy of conventional vaccination. 6,11 The different types of polymers that can be used in controlled release delivery systems to encapsulate antigens and thus protect and control antigen release are listed in Table 2.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, development of more efficient and safe adjuvant / vaccine delivery systems requiring single administration to obtain high and long lasting immune responses is of primary importance. A new generation of more effective adjuvants [9], including liposomes, muramyl peptide and ISCOMs (Immunostimulatory Compounds), have been proposed to replace alum. In recent years there have been various attempts to demonstrate new immunization strategies to induce higher level and larger duration of immune responses following parenteral and / or oral administration.…”
Section: Introductionmentioning
confidence: 99%